Peran Mamak Dalam Pembinaan Akhlak Kemenakan Di Nagari Salibutan Kecamatan Lubuk Alung Kabupaten Padang Pariaman - M. Fauzan; Rengga Satria (Journal on Education, 2023)
This study aims to analyze the role of mamak in fostering the morals of nephews in Nagari Lilinutan, Lubuk Alung District, Padang Pariaman Regency. A qualitative approach is used in uncovering facts from the phenomenon of this research topic, collecting data using observation, interviews and document studies. Furthermore, the data were analyzed using data reduction, data presentation, and drawing conclusions. The validity of the research data was tested using a triangulation technique covering 4 aspects, namely interval validity, internal validity, reliability and objectivity. The results of this study concluded that the morals displayed by nephews in the Nagari Lilinutan were classified as obedient, kind, and controlled by their social level. This is the result of the mamak's central role in providing moral guidance for nephews in accordance with Minangkabau customary law. The supporting factors for the role of mamak in this context include; nephew's self-awareness of the importance of having good morals, government support for customary preservation practices, and mutual respect between mamak and nephew. While the inhibiting factors include family economic factors, the times, social conditions, juvenile delinquency, and disagreements with each other.